Antioxidant activity and acetylcholinesterase inhibition of field and in vitro grown Musa L. species - Ayoola, I.O.; Gueye, B.; Sonibare, M.A.; Abberton, Michael T. (Springer, 2017)
Bananas and plantains (Musa L. species) have medicinal applications against diseases such as hypoglycemia, hypertension, and neurological disorders, especially Alzheimer’s disease. The demand for these plants is growing very fast, resulting in a relatively heavy load on Musaceae genetic resources. The study evaluated and compared the acetylcholinesterase (AChE) inhibition and antioxidant activity of field and in vitro plant materials of nine accessions of Musa spp. consisting of Tropical Musa banana (TMb: TMb 106, TMb 145, TMb 8, TMb 82, TMb 55) and Tropical Musa plantain (TMp: TMp 116, TMp 24, TMp 36) from the International Institute of Tropical Agriculture and Musa sapientum (MS) from the University of Ibadan Botanical garden, Nigeria. Musa accessions were estimated onto Murashige and Skoog (MS) medium supplemented with 0.18 mg/L indole acetic acid (IAA) and 4.5 mg/L benzyl amino purine (BAP). The in vitro grown accessions behaved differently with TMb 8 having the highest average shoot length of 5.03 ± 0.66 cm, and average number of leaves of 5.65 ± 0.38 cm at the end of 6 weeks. Leaf extracts provide more quantity of phenolics, flavonoids and higher 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity than the fruit extracts. The AChEI activity of the field plants ranged from 60.54 ± 0.54 to 98.46 ± 0.09 % and in vitro plants from 61.88 ± 0.11 to 76.60 ± 0.34 % at 200 µg/mL. Crude methanol extract (CME) of the in vitro plants showed higher DPPH antioxidant activity than the field plants with IC50 (extract concentration providing 50 % inhibition) values ranging from 9.57 ± 0.24 to 48.37 ± 0.62 µg/mL compared with CME of the field samples, which had IC50 ranging from 75.86 ± 1.76 to 162.20 ± 3.77 µg/mL. Plant tissue culture can be a reliable alternative cultivation method for mass propagation and conservation of Musa species for the production of antioxidant and acetylcholinesterase metabolites.